2020
DOI: 10.1097/prs.0000000000006914
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medicare Reimbursement for Reconstructive Plastic Surgery Procedures: 2000 to 2019

Abstract: Background: An understanding of financial trends is important to advance agreeable reimbursement models in plastic surgery. This study aimed to evaluate trends in Medicare reimbursement rates for the 20 most commonly billed reconstructive plastic surgery procedures from 2000 to 2019. Methods: The Centers for Medicare and Medicaid Services Physician and Other Supplier Public Use File was used to identify the 20 reconstructive procedures most commonly bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 19 publications
5
70
1
Order By: Relevance
“…A combination of rising physician practice expenses, decreasing microsurgical reimbursement, and relatively high cost and resource requirements required to practice microsurgery Similar trends to those found in the present study have been identified in recent years across numerous surgical fields. [3][4][5][6] Specifically within microsurgical reconstruction, declining reimbursement has been documented for head and neck reconstruction, hand surgery, flap reconstruction, and breast surgery. 12,18,19 Despite overall diminishing reimbursement, the current study indicates a deceleration in the declining reimbursement rates from an average of À23.16% during the 2000s to À3.95% in the following decade (►Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of rising physician practice expenses, decreasing microsurgical reimbursement, and relatively high cost and resource requirements required to practice microsurgery Similar trends to those found in the present study have been identified in recent years across numerous surgical fields. [3][4][5][6] Specifically within microsurgical reconstruction, declining reimbursement has been documented for head and neck reconstruction, hand surgery, flap reconstruction, and breast surgery. 12,18,19 Despite overall diminishing reimbursement, the current study indicates a deceleration in the declining reimbursement rates from an average of À23.16% during the 2000s to À3.95% in the following decade (►Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, the CMS Physician Fee Schedule Look-Up Tool was utilized to collect reimbursement rate data for each CPT code. 3,5,6,14 This tool was chosen as it is the only public tool that provides comprehensive information on over 10,000 services billable to Medicare, including reimbursement, relative value units, and payment modifiers. Modifiers that can impact reimbursement include unilateral versus bilateral procedure, use of an assistant or co-surgeon, return to operating room, and repeat procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature in plastic surgery has reported on data obtained from TrinetX. 16 A literature review was conducted to identify a representative sample of the most common plastic and reconstructive procedures nationally [17][18][19][20] . TrinetX was queried for the associated Current Procedural Terminology (CPT) codes (Table 1) of both inpatient and outpatient operations.…”
Section: Methodsmentioning
confidence: 99%
“…1 This was a longitudinal analysis of reimbursement rates through time for common services, both E/M and procedural, performed by dermatologists to ascertain if trends were similar to other fields studied to date. [2][3][4][5]…”
mentioning
confidence: 99%